2000
DOI: 10.1046/j.1469-1809.2000.6420107.x
|View full text |Cite
|
Sign up to set email alerts
|

Human 18 kDa phosphotyrosine protein phosphatase (ACP1) polymorphism: studies of rare variants provide evidence that substitutions within or near alternatively spliced exons affect splicing result

Abstract: The mammalian low molecular weight phosphotyrosine protein phosphatase is expressed as two distinct isoforms. The human ' fast ' and ' slow ' isoforms differ only in the sequence of an internal segment of 34 residues, and the ACP1 gene contains two adjacent exons (E3F and E3S) which encode these segments. We have previously suggested that the fast and slow isoforms are generated by mutually exclusive pre-mRNA splicing of E3F and E3S. The common alleles ACP1*A, *B and *C express the fast and slow isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…XLPTP1a and XLPTP1b differ from each other only in an internal 36-amino-acid region (positions 42 to 77) (Fig. 1b), suggesting that the two isoforms originate from alternative splicing (46,71).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XLPTP1a and XLPTP1b differ from each other only in an internal 36-amino-acid region (positions 42 to 77) (Fig. 1b), suggesting that the two isoforms originate from alternative splicing (46,71).…”
Section: Resultsmentioning
confidence: 99%
“…Several isoforms of LMW-PTP have been identified in mammals and are believed to result from alternative splicing (18,19,46,50,53,78). These isoforms may have different kinetic characteristics and substrate specificities (15,71).…”
mentioning
confidence: 99%
“…These enzymes are identical, with the exception of 33 amino acids that are the products of the alternatively spliced third and fourth exons, respectively (Dissing and Johnsen 1992). Changes in the amount of F and S isozymes produced by each allele have been associated with mutations that interrupt exonic splicing enhancers (Rudbeck et al 2000). ACP1*C is the only allele to produce more S than F isozyme, and it also produces approximately six times more S isozyme (and somewhat less F isozyme) than any other major allele (Dissing 1987).…”
mentioning
confidence: 99%
“…ACP1*C is the only allele to produce more S than F isozyme, and it also produces approximately six times more S isozyme (and somewhat less F isozyme) than any other major allele (Dissing 1987). These differences in isozyme production have been suggested to be the result of a single silent substitution in the third exon of ACP1*C that alters motifs recognized by human splicing factors SRp40 and SRp55 (Rudbeck et al 2000).Patterns of ACP1 allele frequency variation have been interpreted as evidence that particular genotypes may be adaptive in certain environments. This pattern is most striking for the ACP1*A and ACP1*B alleles.…”
mentioning
confidence: 99%
“…Erythrocyte acid phosphatase (ACP locus 1), also known as low-molecular-weight protein tyrosine phosphatase (LMW-PTP), has previously been associated to hyperglycemia, dyslipidemia, and obesity [1][2][3][4][5][6][7][8][9]. Recently, Pandey et al [4] demonstrated for the first time that ACP1 is a key negative regulator of insulin signaling in vivo.…”
Section: Introductionmentioning
confidence: 99%